Effect of Soil Moisture Level on Yield and Nutrient Balance Sheet of Black Cumin (Bangladesh Journal of Agricultural Research, 2023)
A field experiment was conducted at Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur during rabi season of 2016-17 to evaluate the effects of soil moisture levels on black cumin (BARI Kalozira-1). The study site belongs to Shallow Red-Brown Terrace Soil of Salna series under AEZ-28 (Madhupur Tract). The experiment was set up in randomized complete block design with three replications, comprised five treatments assoil moisture levels: irrigation at 90%, 80%, 70%, 60% and 50% field capacity. The required number and amount of irrigation were 11 and 113.1mm, 8 and 108.1mm, 6 and 104.2mm, 4 and 99.4mm and 0 and 22.4mm in irrigation at 90%, 80%, 70%, 60% and 50% field capacity, respectively. The maximum seed yield (1243.0 kg ha-1) was recorded under the highest moisture regime in irrigation at 90% field capacity of soil moisture. The minimum yield (165.5 kg ha-1) was noted at 50% field capacity (where no irrigation was required). Net nutrient balance of N, K and S showed negative balance but P was positive. The maximum water use efficiency (10.51 kg ha-1 mm-1) for yield was noted with irrigation at 90% field capacity, which may be recommended for black cumin cultivation in the study area. The cost-benefit analyses also indicate that the maximum net income (Tk. 123503.00) of black cumin cultivation has been achieved by maintaining the highest soil moisture through irrigating the crop at 90% of field capacity.Bangladesh J. Agril. Res. 46(1): 43-61, March 2021